A Study on Factors Determining Public Acceptance of Telemedicine in Malaysia's Private Healthcare System - Ramli R.; Yahya H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Developing countries; Health care; Medical informatics; Health informatics; Healthcare; Healthcare services; Healthcare systems; Malaysia; Policy makers; Public acceptance; Quality of health care; Technology acceptance; Telemedicine services; Telemedicine